UPAYA PENINGKATAN KEBERSIHAN GIGI DAN MULUT, PENCEGAHAN DAN PENURUNAN KARIES GIGI PADA PETUGAS KEBERSIHAN KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Amperawati, Metty; Utami, Naning Kisworo; Ulfah, Rasuna (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
The results of research by Anisa, R in 2022 on cleaning staff in the city of Banjarbaru showed that dental and oral health knowledge was still in the poor category, 71% and dental and oral hygiene was 60%, still in the poor category. This is because the janitor has never received education about dental and oral health. The results of the DMF-T examination of the cleaning officers showed that the average DMF-T was 5.8, meaning that each cleaning officer experienced caries in 5-6 teeth ranging from shallow to deep caries, fissures in 15 teeth in the permanent first and second molars. The aim of this Community Service is to increase knowledge, take preventive measures and carry out simple dental care. The method used is to provide education through counseling, dental examinations and dental care. The target of community service is 93 Banjarbaru city cleaning officers. The methods used are counseling, mass tooth brushing, scaling, fissure sealant, and filling. The time period was 2 (two) months, namely September-October 2023. Achievements and Conclusions After implementing Community Service, the target of good knowledge increased to 60%, Dental and Oral Hygiene became good 58.1%, Internal fissures became 1 tooth, Dental caries 97 teeth down to 49 teeth.